Abundance of Soil Arthropods under Reduced Tillage and Bagasse Mulching in a Sugarcane Plantation in Central Lampung, Indonesia - Fransiscus Xaverius Susilo; I Gede Swibawa; Nobuhiro Kaneko; Anastasia Kristina; Muhammad Badrus Sholih; Muhamad Jaya Saputra; Fazri Firdaus; Sri Haryani; Heru Gunito; Saefudin Saefudin (JOURNAL OF TROPICAL SOILS, 2018)
This study was aimed to show whether conservation effort through reduced tillage or mulching can promote soil zoological benefits, especially to the soil arthropods in sugarcane plantations area, Central Lampung, Indonesia. Twenty sugarcane plots of 25 m × 25 m size each were prepared in the area and treated with two combined treatments i.e. tillage (no tillage and full tillage) and mulching (without bagasse and with bagasse mulch). Tillage and planting were done in July 2010 while mulching was conducted in August 2010. The arthropods were sampled using pitfall traps (mouth diameter = 13.5 cm), each was set per plot for 24 hours. Specimens were identified at least to order level. Sampling was done in September 2010 (1 month after mulch treatment, MAT), January 2011 (4 MAT), and July 2011 (10 MAT). We found four major arthropod orders, namely Araneae (spiders, predator), Coleoptera (beetles, mostly non predator), Collembola (springtails, fungal feeder), and Hymenoptera (ants, mostly forager). The last two groups were the most dominant (contributing to > 90 % of the total abundance). Tillage affected the abundance of overall soil arthropods at 1 MAT and 4 MAT but the effect disappeared at 10 MAT. Reduced tillage can conserve, or does not harm, some soil arthropod groups (ants, predatory ants, beetles, springtails, spiders) in sugarcane agroecosystem.